(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
Arabica coffee (Coffea arabica) cultivation in the medium altitude (700-900 m above sea level, asl.) will face problems such as decreasing productivity, physical, biochemical and cup quality and increasing intensity of pest and diseaseattacks. Utilization of plant material that has good productivity and cup quality, resistance to pests and diseases is an effort that can be done to overcome theseproblems. The aims of this study is to evaluate performance of Arabica coffee quality grown at high and medium altitude area, as well as biochemical compound and cup quality changes that occur due to influence of genotypes and genotype Ã— altitude interactions. Eight genotypes of Arabica coffee were evaluated at two locations namely KP Andungsari (1,250 m asl.) and Kalibendo (700 m asl.). The field design for each location was randomized complete block design with three replicates. Observations were made on the two quality aspects, namely the biochemical compounds and cup qualities. The result on the biochemical compounds showed that the altitude significantly affect to the content of caffeine, sucrose, and trigonelline. Effect of genotype Ã— altitude occured to the caffeine, trigonelline, and sucrose content. Diversity of chlorogenic acid content was caused by the genotype effect. Cup test results showed that genotypes grown at high altitude had a better cup quality than genotypes on medium altitude. Cup quality variables that were changed due to altitude difference were fragrance and aroma, flavor, aftertaste, acidity, balance, and overall, while the cup quality variable that did not changed was the body. Characters of coffee aroma at the high altitude were floral, spicy and fruity, while at the medium altitude were herbal, green and grassy. The best quality genotype at the high altitude was K8, while at the medium altitude was K29. Environment (altitude) gives greater influence to the formation of coffee flavor variations produced compared to genotypes.